(untitled) (Simbiótica. Revista Eletrônica, 2016)
This study aims to analyze six images on the same theme and figure produced by Italian photographer and publicist Oliviero Toscani, for Benetton brand campaigns. The selected images are inserted in the book “Advertising is smiling carrion” . The theoretical framework of French semiotics and its development of plastic and semi-semiotic symbolism will use should be made. The selected images were produced for the collection of the brand United Colors of Benetton between 1989 to 1993 and address issues of social, political and religious. Therefore, try to describe the meaning constructed in noverbal through plastic semiotics and semissimbolismo. Keywords: photography; advertising; semiotic-plastic; semi-symbolism.